Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1371/journal.pone.0045918
|View full text |Cite
|
Sign up to set email alerts
|

Lamin A/C Mutants Disturb Sumo1 Localization and Sumoylation in Vitro and in Vivo

Abstract: A-type lamins A and C are nuclear intermediate filament proteins in which mutations have been implicated in multiple disease phenotypes commonly known as laminopathies. A few studies have implicated sumoylation in the regulation of A-type lamins. Sumoylation is a post-translational protein modification that regulates a wide range of cellular processes through the attachment of small ubiquitin-related modifier (sumo) to various substrates. Here we showed that laminopathy mutants result in the mislocalization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 43 publications
3
31
0
Order By: Relevance
“…3a). These findings suggest that defective lamin A sumoylation could possibly contribute to the pathogenesis of familial dilated cardiomyopathy (DCM) in patients carrying lamin A E203G and E203K mutations 96 . Similarly, several DCM-causing lamin A mutants (D192G, Q353K, R386K) formed SUMO-1-containing aggregates 96 .…”
Section: Sumoylation: a Conserved Ptm For Ifsmentioning
confidence: 98%
See 2 more Smart Citations
“…3a). These findings suggest that defective lamin A sumoylation could possibly contribute to the pathogenesis of familial dilated cardiomyopathy (DCM) in patients carrying lamin A E203G and E203K mutations 96 . Similarly, several DCM-causing lamin A mutants (D192G, Q353K, R386K) formed SUMO-1-containing aggregates 96 .…”
Section: Sumoylation: a Conserved Ptm For Ifsmentioning
confidence: 98%
“…These findings suggest that defective lamin A sumoylation could possibly contribute to the pathogenesis of familial dilated cardiomyopathy (DCM) in patients carrying lamin A E203G and E203K mutations 96 . Similarly, several DCM-causing lamin A mutants (D192G, Q353K, R386K) formed SUMO-1-containing aggregates 96 . As these mutants also increased overall nuclear protein sumoylation, it is possible that the sequestered SUMO-1 may have been conjugated to other proteins, to which access by desumoylases may have been prevented by the aggregation.and/or prevented the access of desumoylases to these targets.…”
Section: Sumoylation: a Conserved Ptm For Ifsmentioning
confidence: 98%
See 1 more Smart Citation
“…A subset of FPLD cases, also called Dunnigan-type familial partial lipodystrophy, or familial partial lipodystrophy type 2 (FPLD2), is caused by mutations in LMNA gene encoding structural nuclear proteins Lamin A and C (Cao and Hegele 2000; Speckman et al 2000). Lamin A/C is sumoylated (Boudreau et al 2012; Zhang and Sarge 2008) and also binds SUMO through a SUMO-interacting motif (SIM) (Moriuchi et al 2016). Lamin A mutations linked to familial partial lipodystrophy alter lamin A sumoylation (Simon et al 2013).…”
Section: 3 Sumo In Familial Partial Lipodystrophymentioning
confidence: 99%
“…The first hint that lamins were sumoylated came from two‐hybrid experiments showing that lamin A interacted with the SUMO E2 conjugating enzyme, Ubc9p [Zhang et al, ]. Subsequent studies have since confirmed this finding, but with several noteworthy differences between them [Zhang et al, ; Boudreau et al, ; Simon et al, ].…”
Section: Sumo and The Cytoskeletonmentioning
confidence: 99%